Grammatical Metaphor in Scientific Discourse - Sušinskienė, Solveiga (Kalbotyra, 2004)
The term grammatical metaphor is new in linguistics. It was introduced by M.A.K. Halliday in his monograph “An Introduction to Functional Grammar” (1985). The present paper concentrates on nominalized non-gerundive material processes, their semantic and syntactic functions in scientific discourse. Semantically, the sentence functions as a grammatical device for describing a situation. A situation typically consists of three components: processes, participants and circumstances. Sentences which encode the information are of two types: semantically congruent, when the semantic functions play primary syntactic roles, and semantically non-congruent, when semantic functions play secondary syntactic roles. This type of change of semantic functions is called grammatical metaphorization, and the syntactic unit that demonstrates this change is a grammatical metaphor. Grammatical metaphors can be inherent (obligatory) and non-inherent (non-spatial and spatial). Non-inherent semantic functions are more common in scientific discourse. The pragmatic usefulness of the process of metaphorization can be accounted for by the fact that it allows us to make more participants. The use of such participants has the effect of condensing information within the sentence; it contributes to language economy and often serves as a means of cohesion.